Food safety in eating establishments: Assessing conformance of eating establishments to food safety and standards regulations - Surinder Kumar; Puja Dudeja; Prerna Shankar; Simrandeep Kaur (Wolters Kluwer Medknow Publications, 2021)
Introduction: In view of the rising burden of the foodborne illnesses and the rise of eating out culture in India, food safety has assumed greater significance. The Food Safety and Standards Authority of India has prescribed food safety and standards regulations (FSSRs) for commercial eating establishments (EEs). The present study was carried out to ascertain conformance of the EEs to these regulations. Methodology: It was a cross-sectional study conducted on 74 EEs in a metro city in western Maharashtra from May to October 2019 using an interviewer-administered study tool based on FSSR 2011. The study tool covered critical domains such as food hygiene, equipments, health and personal cleanliness, training of food handlers, and product information. Results: Seventy-four EEs included 29 restaurants, 21 bakeries, and 24 snack bars. The score ranged between 42.3% and 73.3%. Of 74, 20 (27%) EEs were placed in poor category (score <50%), Only 3 EE scored >70% and were rated as very good. Only 13 (17.6%) EEs were cleaning the food contact surfaces adequately, i.e. before and after each use, whereas 38 (51.4%) were not cleaning food contact surfaces at least daily. The knowledge regarding food handlers as potential carriers of disease was poor with 60.81% of the respondents having no knowledge about it. Conclusion: The study found significant gaps in EEs with respect to studied food safety domains of FSSR 2011.